1988
DOI: 10.1046/j.1537-2995.1988.28488265260.x
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunization to D antigen and HLA in D‐negative immunosuppressed oncology patients

Abstract: D-negative patients may be divided into responders and nonresponders when immunized with D-positive red cells (RBC). Forty-nine D-negative oncology patients who received D-positive RBCs via platelet and white cell transfusions were studied to determine if nonresponders to D were likely to form lymphocytotoxic antibody (LCA). Nine patients developed anti-D in 16 to 390 days (mean = 112) after 2.6 to 481 ml (mean = 106) of D-positive RBCs. Forty patients had no evidence of anti-D after 0.8 to 535 ml (mean = 98) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 6 publications
3
45
1
2
Order By: Relevance
“…Lichtiger et al postulated that the more intense chemotherapeutic regimens available in the early 1980s impaired the response to D antigen presentation 5 . However, Baldwin et al 3 found when reviewing the records of D− oncology patients transfused between 1979 and 1983 that 18 percent of those given a combination of pooled whole blood‐derived platelet concentrates and apheresis platelets containing 2.6 to 481.2 mL RBCs from D+ donors developed anti‐D. Thirty‐two percent of these patients developed HLA alloimmunization.…”
mentioning
confidence: 99%
“…Lichtiger et al postulated that the more intense chemotherapeutic regimens available in the early 1980s impaired the response to D antigen presentation 5 . However, Baldwin et al 3 found when reviewing the records of D− oncology patients transfused between 1979 and 1983 that 18 percent of those given a combination of pooled whole blood‐derived platelet concentrates and apheresis platelets containing 2.6 to 481.2 mL RBCs from D+ donors developed anti‐D. Thirty‐two percent of these patients developed HLA alloimmunization.…”
mentioning
confidence: 99%
“…Some authors reported no incidence of anti-D alloimmunization in this group of patients [84,86,87,90,91,92,93,94,95]; other authors, however, reported an incidence of anti-D alloimmunization that ranged from 2.7 to 18.7% [83,88,89,108]. …”
Section: Part 2: Plt Transfusion and The D Antigenmentioning
confidence: 88%
“…If we exclude those patients, the percentage of D alloimmunization varies as shown in table 3. Overall, the incidence of D alloimmunization in immunosuppressed patients after D incompatible platelet transfusions is reported to be between 0 and 19% [83,84,85,86,87,88,89,90,91,92,93,94], but keeping some recently published data in mind [95], we can conclude that the frequency of anti-D alloimmunization actually ranges between 0 and 6.8% [96]. …”
Section: Part 2: Plt Transfusion and The D Antigenmentioning
confidence: 95%
See 1 more Smart Citation
“…As ABO antigens are present on platelets, it is preferable to transfuse with ABO compatible platelets [34,37,38]. The concomitant administration of at least 250 IU of anti-D is recommended in case of transfusion of Rh(D) positive platelets to a Rh(D) negative patient to prevent Rh D alloimmunization [39][40][41][42]. Apheresis platelets are recommended to prevent HLA alloimmunisation and platelet refractoriness in patients who require prolonged platelet support [43][44][45][46][47][48].…”
Section: Platelet Transfusionsmentioning
confidence: 99%